2021
DOI: 10.1186/s40168-020-00992-w
|View full text |Cite
|
Sign up to set email alerts
|

Accurate identification and quantification of commensal microbiota bound by host immunoglobulins

Abstract: Background Identifying which taxa are targeted by immunoglobulins can uncover important host-microbe interactions. Immunoglobulin binding of commensal taxa can be assayed by sorting bound bacteria from samples and using amplicon sequencing to determine their taxonomy, a technique most widely applied to study Immunoglobulin A (IgA-Seq). Previous experiments have scored taxon binding in IgA-Seq datasets by comparing abundances in the IgA bound and unbound sorted fractions. However, as these are r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 59 publications
0
33
0
Order By: Relevance
“…In comparison, previous studies used the ratio of the relative abundance of IgA+ and IgAbacteria (Palm et al, 2014) or an IgA binding index (Kau et al, 2015) to define which microbes are targeted by IgA, each of which has drawbacks. The Bayesian approach provides several important advantages compared to other methods including avoiding artifactual associations based on different relative abundances of ASVs, increased power to detect differences in antibody binding to specific ASVs between experimental groups and lower coefficients of variation (Jackson et al, 2021). This study reveals clear connections at the level of common microbial targets across the mucosal (IgA and IgM) and systemic (IgG) antibody networks.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In comparison, previous studies used the ratio of the relative abundance of IgA+ and IgAbacteria (Palm et al, 2014) or an IgA binding index (Kau et al, 2015) to define which microbes are targeted by IgA, each of which has drawbacks. The Bayesian approach provides several important advantages compared to other methods including avoiding artifactual associations based on different relative abundances of ASVs, increased power to detect differences in antibody binding to specific ASVs between experimental groups and lower coefficients of variation (Jackson et al, 2021). This study reveals clear connections at the level of common microbial targets across the mucosal (IgA and IgM) and systemic (IgG) antibody networks.…”
Section: Discussionmentioning
confidence: 92%
“…In this study, we developed an integrated approach (mFLOW-Seq) to simultaneously define the specific microbial targets of local secretory IgA and IgM and systemic IgG in children with IgA deficiency and their unaffected siblings, in addition to the host immunophenotype, investigating the impact of IgA deficiency on both cytokine milieu and lymphocyte subset presence and activation state. In our analysis of antibody targets, we adapted a Bayesian analytic approach (Jackson et al, 2021) to determine the probability of binding by each antibody isotype (i.e., IgA, IgM and IgG) to provide an intuitive and specific measure of antibody targeting across multiple isotypes. In comparison, previous studies used the ratio of the relative abundance of IgA+ and IgAbacteria (Palm et al, 2014) or an IgA binding index (Kau et al, 2015) to define which microbes are targeted by IgA, each of which has drawbacks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A major challenge to accurately characterise low biomass communities is contamination from external sources. A recent study using flow cytometry has also reported the enrichment of low abundance contaminant reads in their sorted samples [ 68 ]. Contamination could potentially occur during sorting and/or library preparation [ 69 ].…”
Section: Discussionmentioning
confidence: 99%